Implementation of the 'Urf Method in Determining Nisab Safar Limit - Haerul Amil; Azman Arsyad (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
This research aims to analyze the use of the 'urf method in determining the safar limit as the area of debate among textualist and contextualist scholars. The problems proposed include (1) what are the opinion differences in terms of the nisab safar limit and (2) the use of the 'urf method in safar and its fiqh rules. This is library research by examining classical literature (turāś) that become monumental works of scholars. The results showed that the prevailing custom accommodated as 'urf is used as a method of discovering Islamic law. This method originated from the habits and understanding of a community group. 'Urf is implemented as a source of Islamic law when it fulfills strict requirements. Therefore, it is used as a method that can solve the problem but the Prophet Muhammad in several hadiths never explicitly stated the nisab safar. This is because it allows the 'urf to be used as one of the perspectives in determining the nisab safar as described by Ibn Taimiyah and Ibn Hazm. The method is expected to be a solution for Muslims living in the technology era and life sophistication.